Opisthopus transversus Rathbun 1893 - Campos, Ernesto (Zenodo, 2016)
Opisthopus transversus Rathbun, 1893 (Figs. 3 F–I, 4A–D) Material examined and new hosts. 1 female, Nov. 2014, from commercial catches, Ensenada shellfish market, collected in Punta Colonet, Ensenada, Baja California, Mexico (30°57'43.65"N, 116°19'22.44"W) in Tivela stultorum . Distribution. Santa Cruz, California, U.S. A to Laguna de San Ignacio, Baja California Sur, Mexico (Campos & Manning 2000). Hosts. Symbiont in the giant Pacific chiton Cryptochiton stelleri (von Middendorff, 1847); the gastropods Aplysia vaccaria Winkler, 1955, Bulla gouldiana Pilsbry, 1895, Conus californicus Reeve, 1844, Lithopoma undosum (Wood, 1828) [= Megastraea undosa (W. Wood)], Megathura crenulata (Sowerby I, 1825), Navanax inermis (J. G. Cooper, 1862), and Neverita lewisii (Gould, 1847); the bivalves Atrina tuberculosa (G. B. Sowerby I, 1835), Crassadoma gigantea (J.E. Gray, 1825), Crassostrea gigas (Thunberg, 1793), Megapitaria squalida (G. B. Sowerby I, 1835), Modiolus capax , Modiolus sp., Mytilus edulis (see below), Nuttallia nuttallii , Pholas sp., Platyodon sp., Pseudochama exogyra (Conrad, 1837), Tivela stultorum , Tresus nuttallii , Zirfaea sp., and Zirfaea pilsbryi Lowe, 1931. Also commensal in the tube of the polychaete Chaetopterus variopedatus (Renier, 1804), and the cloaca of the holothuroids Apostichopus californicus (Stimpson, 1857), A. parvimensis (Clark, 1913), and Molpadia arenicola (Stimpson, 1857), (Schmitt et al. 1975; Garth & Abbott 1980; Ricketts et al . 1980; Campos et al. 1992). Other hosts. Garth & Abbott (1980) recorded the species in the Atlantic bivalve Dinocardium robustum (Lightfoot, 1786), but the presence of this bivalve in the eastern Pacific should be confirmed. Likewise, the record of Mytilus edulis needs confirmation since this species is validly reported only from embayments in California U.S.A. Mytilids from open coastal area may belong to M. galloprovincialis or M. trossulus . Remarks. According to Hopkins & Scanland (1964) the occurrence of O. transversus in multiple host ...